Evaluation of 2′-Deoxy-2′-Flouro-5-Methyl-1-β--Arabinofuranosyluracil as a Potential Gene Imaging Agent for Expression In Vivo - Mian M. Alauddin; Atranik Shahinian; Erlinda M. Gordon; Peter S. Conti (Molecular Imaging)
2′-Deoxy-2′-flouro-5-methyl-1-β- d -arabinofuranosyluracil (FMAU) has been evaluated in HT-29 cells as a potential positron emission tomography (PET) radiotracer for imaging HSV-tk gene expression in vivo. In vitro experiments demonstrate that the accumulation of [ 14 C]-FMAU in HSV-tk -expressing cells is 2.4-fold ( p < .02), 4.0-fold ( p < .001), and 5.3-fold ( p < .001) higher than the wild-type cells at 1, 3, and 5 hr, respectively. In vivo studies revealed that the tumor uptake in HSV-tk -expressing cells was 2.3-fold ( p < .001), 3.0-fold ( p < .001), and 5.5-fold ( p < .001) higher than the control cells at 1, 2, and 5 hr, respectively. FMAU was found to be more sensitive compared to our earlier studies using 9-[(3- 18 F-fluoro-1-hydroxy-2-propoxy)methyl]-guanine ([ 18 F]-FHPG) and 9-(4-[ 18 F]-fluoro-3-hydroxy-methylbutyl)guanine ([ 18 F]-FHBG) in the same cell lines, although, the specificity was less than FHBG. These results suggest that while FMAU labeled with PET isotopes may be useful for imaging HSV-tk -expressing tumors in vivo, multitracer studies across additional tumor models are necessary in order to identify an optimal PET radiotracer.